The Influence of Peer-Correction Techniques on the Ability to Write Explanatory Texts in Students of Taruna Maritim Vocational School - Gabriel Marbun, Anugerah Septian; Naelofaria, Salmah (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Writing skills, especially writing explanatory texts, are an important aspect in mastering Indonesian at the vocational high school level. However, students often have difficulty in developing ideas and following complex language rules. This study aims to examine the influence of writing techniques peer-correction in improving the ability to write explanatory texts of class XI students of SMK Taruna Maritim Dirgantara Medan. Based on the results of observations, it was found that conventional and teacher-centered learning methods caused students to have a poor understanding of the mistakes in their writing. Peer-correction allows students to be more active in the learning process by giving each other feedback on their friends' writing. By applying this technique, it is expected that there will be a significant increase in writing skills, as well as a growing sense of responsibility and student activeness in learning.